Análisis de los incentivos tributarios de la florícola Joseth & Maximilian Flowers S.A. En el período 2018. - Arévalo Cabezas, Liz Morelia (2020)
This research work was based on the analysis of tax incentives and benefits for companies in the agricultural sector, because they are tools that stimulate investment and allow businesses to obtain greater profitability, reducing their tax burden to a certain extent. The main problem of Florícola Joseth & Maximilian Flowers S.A., is in a certain way the lack of knowledge in updates of tributary matter and the scarce identification of tributary incentives that can be applied, that is why this investigation was focused in making a study of the tributary incentives and benefits that the floriculture can apply in the period 2018. This project was carried out under a quantitative approach of exploratory type, documented through an interview with the company's accountant, and comparative tables such as worksheets, adjustments, among others. We analyzed the information obtained from taxes declared by the company, versus the application of the tax regulations in force to date, and which are framed in the reality of the floriculture industry, in a practical exercise applied to the tax reconciliation of 2018, with the objective of letting it know the tax benefit it could benefit from.